Analyses of organic grain prices - Heiman, Ross D. (Kansas State University, 2006)
Organic has become a familiar term in agriculture, usually bringing to mind the phrases “no chemicals” and “large premiums.” While organic products usually command a substantial price premium over their conventional counterparts, the determinants of this premium are generally unknown. The lack of literature covering organic prices is not from a lack of interest but from a lack of information and data for organic commodities. This study examines two aspects of organic grain prices in an attempt to learn more about the organic grain sector. The first objective was to identify determinants of organic premiums received by members of a Kansas organic grain cooperative. Six different grains along with alfalfa hay were examined using hedonic models and bootstrapping statistical techniques. Findings of the hedonic analyses are as follows. Dairy farms seemed to pay a lower premium for feed grade corn and hard red winter wheat compared to other types of buyers. Buyers located in Kansas tended to provide a smaller premium than buyers located elsewhere. Early contract periods produced a smaller premium than later periods. Shipment timing was much the same, with fourth quarter shipments receiving the largest premium. Additionally, each subsequent contract year resulted in a larger premium. If the cooperative had arranged shipment of the commodity, a lower premium was acquired. Finally, longer contract lengths resulted in a larger premium. The second part of this study examined various price series of organic and conventional commodities to determine if the two markets were related. Using vector autoregressive models, cointegration and causality tests were conducted, and speed of adjustment to a shock in the long run equilibrium and exogeneity were also examined. Of the 43 pairs of organic and conventional price series tested, 29 were found to be cointegrated. Of those cointegrated pairs, 11 causal relationships were found. Five of these causal relationships indicated that the conventional commodity prices led the organic. There were six instances where the organic commodity prices were found to lead the conventional. For most causal relationships, about 5% of the adjustment to a shock, or divergence from long run equilibrium occurred in one week.
Keywords: Organic grain; Hedonic; Autoregressive; Cointegration; Causal; Agriculture, General (0473); Economics, Agricultural (0503)